2019 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD) 2019
DOI: 10.1109/nusod.2019.8806793
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and optical properties of 2D hexagonal Boron Arsenide

Abstract: Group theory and density functional theory methods are combined to obtain compact and accurate k · p Hamiltonians that describe the bandstructures around the K and Γ points for the 2D material hexagonal boron arsenide (h-BAs) predicted to be an important low-bandgap material for electric, thermoelectric, and piezoelectric properties that supplements the well-studied 2D material hexagonal boron nitride. Hexagonal boron arsenide is a direct bandgap material with band extrema at the K point. The bandgap becomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Mathias et al examined the electronic structure and optical properties of the h-BAs monolayer by k.p theory, and DFT. 33 They calculated the band gap which obtained 0.74 eV and also showed that the optical properties were adjustable by applying an electric field and strain. 29 In this study, we investigate the thermoelectric and electronic properties of the h-BAs monolayer and bilayer using the tight binding model and the Green function approach.…”
mentioning
confidence: 99%
“…Mathias et al examined the electronic structure and optical properties of the h-BAs monolayer by k.p theory, and DFT. 33 They calculated the band gap which obtained 0.74 eV and also showed that the optical properties were adjustable by applying an electric field and strain. 29 In this study, we investigate the thermoelectric and electronic properties of the h-BAs monolayer and bilayer using the tight binding model and the Green function approach.…”
mentioning
confidence: 99%